The Treatment of Hourly Elevations of the Tide using an IBM 1620 - Lennon, G. W. (The International Hydrographic Review, 2015)
At the Tidal Institute in recent months there has been assembled a family of mutually compatible computer programs for the treatment of tidal elevations at hourly intervals. These programs are written for the IBM 1620 computer and deal with the analysis and prediction of tidal elevations together with the extraction of residuals. In view of the comparatively small size and limited speed of this computer in relation to those more frequently favoured by workers in the tidal field, every attempt has been made to optimise the programs with the result that their ability to execute the tidal calculations can be compared with programs designed for more powerful computers. The aim has been to reduce the bulk of calculation at the expense of more elaborate programming, and without any reduction in precision.